Dynamic pricing in electricity and natural gas distribution networks: An EPEC model. (15th September 2020) - Chen, Sheng; Sun, Guoqiang; Wei, Zhinong; Wang, Dan
Abstract: Independent clearing of coupled retail electricity and natural gas markets generally results in a loss of market efficiency. This study investigates the problem of dynamic pricing in retail electricity and natural gas markets in the presence of network constraints by developing a two-leader multiple-follower bi-level model. Here, upper-level electricity and gas utility companies serve as leaders in the model, and determine their optimal dynamic retail prices in anticipation of the demand response (DR) provided by multiple lower-level integrated third-party DR providers or aggregators. Moreover, the model considers the dynamic gas prices provided by gas utility companies to electric utility companies for distributed gas-fired power units, which coordinates the operations of the separate utilities. The resulting model is recast as an equilibrium problem with equilibrium constraints (EPEC). Numerical results for a test system composed of an electric grid with distributed gas-fired power units, a gas distribution network, and multiple integrated DR aggregators indicate that the economic value of the proposed dynamic pricing scheme is up to 5.5% compared with existing regular pricing schemes. Highlights: We model the interaction between electricity/gas utilities and DR aggregator. . We utilize dynamic gas prices to coordinate the operations of and gas utilities. . The problem is modeled as a two-leader multiple-follower bi-level structure. . The economic value of the proposed dynamic pricing scheme is verified. .